1998
DOI: 10.1038/sj.bjp.0701831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pravastatin on cholesterol metabolism of cholesterol‐fed heterozygous WHHL rabbits

Abstract: 1 We administered the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor pravastatin at a daily dose of 1 mg kg 71 body weight to cholesterol-fed (0.03%) heterozygous Watanabe heritable hyperlipidaemic rabbits, an animal model for heterozygous familial hypercholesterolaemia. 2 After 12 months of cholesterol treatment, immunohistochemistry with the monoclonal antibody 9D9 was used to detect hepatic low density lipoprotein (LDL) receptors, which were quanti®ed by densitometry. In addition we determined LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…61 In addition to these 2 models, a substrain of WHHL was created for examination of robust coronary atherosclerosis. 62 There are also several rabbit transgenic models that modify atherosclerosis, including apoE deficiency. 63 Overall, rabbits can be cost equivalent to mice at purchase, although they are more expensive to house and feed.…”
Section: Rabbitsmentioning
confidence: 99%
“…61 In addition to these 2 models, a substrain of WHHL was created for examination of robust coronary atherosclerosis. 62 There are also several rabbit transgenic models that modify atherosclerosis, including apoE deficiency. 63 Overall, rabbits can be cost equivalent to mice at purchase, although they are more expensive to house and feed.…”
Section: Rabbitsmentioning
confidence: 99%
“…It is worth noting that in previous studies heterozygous WHHL rabbits showed spontaneous atherosclerotic lesions [10]which were not observed until at least 2 years of age [11]. In heterozygous WHHL from another breeding, serum cholesterol levels in the range of those from control NZW fed a standard diet were found so that a 0.03% cholesterol-enriched diet was needed to facilitate lesion development [12, 13]. We can speculate that, due to spontaneous selection, there is a more or less remarkable deficit in the hepatic LDL receptor in inbred animals which in turn makes heterozygous WHHL rabbits more or less prone to developing early lesions.…”
Section: Discussionmentioning
confidence: 99%